Synthesis of an Isomer of Chaulmoogric Acid - Limaye, P.A.; Ghate, S.M. (Asian Journal of Chemistry, 2010)
An isomer of Chaulmoogric acid has been synthesised from methyl ricinoleate obtained from castor oil, —the commercial commodity.